1995
DOI: 10.1007/bf01289505
|View full text |Cite
|
Sign up to set email alerts
|

Systematic studies of fission fragment kinetic energy distributions by Langevin simulations

Abstract: Abstract. Fission fluctuation-dissipation dynamics of heavy nuclei has been studied using Langevin Monte Carlo simulations. The covariant form of the fission transport equation and the coefficients related to it are investigated. To learn about the influence of the dynamics from the ground state to the saddle point on the kinetic energy distributions we have studied various systems and compared the calculations both starting from the ground state and from the saddle point. Both the mean total kinetic energy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…This parametrization has been also used for static calculations performed with the Strutinsky shell correction method [92], dynamic calculations of MEDs in the diffusion model [12], and for calculating a large number of different fission characteristics in the Langevin approach [19,20,[107][108][109]. The parameter c describes nuclear elongation (the nuclear length, in units of the initialsphere radius R 0 , is equal to 2c), the parameter h defines neck-thickness variation for a given elongation, and the coordinate α sets the ratio between the masses of future fragments.…”
Section: The Model and Basic Equations 21 Parametrization Of Nuclearmentioning
confidence: 99%
See 1 more Smart Citation
“…This parametrization has been also used for static calculations performed with the Strutinsky shell correction method [92], dynamic calculations of MEDs in the diffusion model [12], and for calculating a large number of different fission characteristics in the Langevin approach [19,20,[107][108][109]. The parameter c describes nuclear elongation (the nuclear length, in units of the initialsphere radius R 0 , is equal to 2c), the parameter h defines neck-thickness variation for a given elongation, and the coordinate α sets the ratio between the masses of future fragments.…”
Section: The Model and Basic Equations 21 Parametrization Of Nuclearmentioning
confidence: 99%
“…The total kinetic energy-distribution parameters have been investigated for various nuclei in a large number of experimental [182][183][184] and theoretical [107,173,185,186] studies. From an analysis of the available experimental data, it was found that E K is virtually independent of both angular momentum and an excitation energy [182].…”
Section: Energy Distribution Of Fission Fragmentsmentioning
confidence: 99%
“…The first two moments of the energy distribution are studied both in many experimental [4,51,60] and theoretical works [18,59,61,62]. Analysis of experimental data shows that the average kinetic energy of fragments E K depends very little on either angular momentum or excitation energy [4].…”
Section: The First and The Second Moments Of The Energy Distributionmentioning
confidence: 98%
“…The last equation means that a part of the Coulomb repulsion energy is used to overcome nuclear attraction between the nascent fragments. It can be estimated as in [31,32].…”
Section: Details Of the Modelmentioning
confidence: 99%